Evidence from a Natural Experiment on the Development Impact of Windfall Gains: The Camisea Fund in Peru - Leonardo Corral; Heath Henderson; Juan Jose Miranda (Inter-American Development Bank (IDB), 2016)
This document studies the economic effect of windfall gains by examining a Peruvian natural experiment. The Camisea Fund for Socioeconomic Development (FOCAM) is an inter-governmental fiscal transfer scheme that allocates natural gas royalties generated by the Camisea Gas Project to eligible subnational governments. We exploit the rules governing FOCAM allocation to identify the effect of the transfers on municipal accounts, local infrastructure, and economic development. Using a newly constructed district- level dataset for the years 2005 and 2012, we find evidence of positive impacts on municipal capital expenditures and local infrastructure. However, we also find evidence of a negative impact on municipal current expenditures. More specifically, we find that municipalities with low absorptive capacity coped with the increased administrative burden of FOCAM transfers by reallocating administrative effort toward (away from) executing capital (current) expenditures.
hdl:11319/7520
Keywords: C14; H70; O10; O54; Q32; 330; Inter-governmental Fiscal Transfers; Natural Experiment; Peru; Windfall Gains